2005
DOI: 10.1063/1.1992481
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid phase transitions in supercooled water studied by computer simulations of various water models

Abstract: Liquid-liquid and liquid-vapor coexistence regions of various water models were determined by MC simulations of isotherms of density fluctuation restricted systems and by Gibbs ensemble MC simulations. All studied water models show multiple liquid-liquid phase transitions in the supercooled region: we observe two transitions of the TIP4P, TIP5P and SPCE model and three transitions of the ST2 model. The location of these phase transitions with respect to the liquid-vapor coexistence curve and the glass temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
160
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(185 citation statements)
references
References 77 publications
20
160
0
5
Order By: Relevance
“…The coincidence of T Â with T p within the error bars indicates that the behavior of the protein is strongly coupled with the behavior of the surrounding solvent, in agreement with recent experiments [51]. Note that T Â is much higher than the glass transition temperature, estimated for TIP5P as T g ¼ 215 K [72]. Thus this crossover is not likely to be related to the glass transition in water.…”
Section: Article In Presssupporting
confidence: 74%
“…The coincidence of T Â with T p within the error bars indicates that the behavior of the protein is strongly coupled with the behavior of the surrounding solvent, in agreement with recent experiments [51]. Note that T Â is much higher than the glass transition temperature, estimated for TIP5P as T g ¼ 215 K [72]. Thus this crossover is not likely to be related to the glass transition in water.…”
Section: Article In Presssupporting
confidence: 74%
“…Indeed, it appears that the hypothesized liquid-liquid phase transition is below, or at least close to, the glass transition temperature. A recent simulation analysis of the orientational dynamics of water at fixed density [47] has shown that the temperature of dynamical arrest of the system, defined by the mode coupling theory, is relatively close in temperature and density to recent estimate of the liquid-liquid critical point [73]. However, as we have shown here, the study of the Widom line at temperatures above the liquid-liquid critical point could represent a useful way to investigate the inaccessible part of the supercooled phase diagram of water.…”
Section: Discussionmentioning
confidence: 99%
“…Direct experimental evidences of this phenomenon have been observed in liquid phosphorous [1,2] and triphenyl phosphite [3], while consistent data exists for water [4,5,6,7,8], silica [9,10], aluminate liquids [11], selenium [12], and cobalt [13], among others [14]. Simulations predict a liquid-liquid critical point for supercooled water [15,16,17,18,19,20,21], phosphorous [22], supercooled silica [9,23,24], and hydrogen [25]. For other substances, such as carbon, literature is contradictory [26,27,28].…”
Section: Introductionmentioning
confidence: 99%